Answer:
g and f are inverse functions because g(f(x)) = f(g(x)) = x
Step-by-step explanation:
Let's start by finding f(g(x)) and g(f(x)). As we discussed in another question, to find a composite function, apply the outer function to whatever the inner function evaluates to. We can start with f(g(x)):
![f(g(x))=f(\frac{x+6}{7})=7(\frac{x+6}{7} )-6=x+6-6=x](https://tex.z-dn.net/?f=f%28g%28x%29%29%3Df%28%5Cfrac%7Bx%2B6%7D%7B7%7D%29%3D7%28%5Cfrac%7Bx%2B6%7D%7B7%7D%20%29-6%3Dx%2B6-6%3Dx)
Now, let's find g(f(x)):
![g(f(x))=g(7x-6)=\frac{(7x-6)+6}{7} =\frac{7x}{7}=x](https://tex.z-dn.net/?f=g%28f%28x%29%29%3Dg%287x-6%29%3D%5Cfrac%7B%287x-6%29%2B6%7D%7B7%7D%20%3D%5Cfrac%7B7x%7D%7B7%7D%3Dx)
There is a property that says that if f(g(x)) = g(f(x)) = x, the two functions are inverse. This suggests that g and f are inverse functions. We can verify this by taking one function, switching y and x, and then solving for y. If we complete this process and find that we get the OTHER function, it means the two functions are inverse. Let's try that:
![f(x)=y=7x-6](https://tex.z-dn.net/?f=f%28x%29%3Dy%3D7x-6)
Swap x and y:
![x=7y-6](https://tex.z-dn.net/?f=x%3D7y-6)
Solve for y:
![x+6=7y\\y=\frac{x+6}{7}](https://tex.z-dn.net/?f=x%2B6%3D7y%5C%5Cy%3D%5Cfrac%7Bx%2B6%7D%7B7%7D)
Notice that we got g, which means f and g are inverse.
Answer:
2^3
Step-by-step explanation:
you subtract the exponents if they have the same coefficient when dividing them.
9-6=3
<h3>
Answer: 9/41</h3>
==========================================================
Explanation:
We have a triangle with these three sides.
Use the pythagorean theorem to find b
a^2+b^2 = c^2
b = sqrt(c^2 - a^2)
b = sqrt(82^2 - 80^2)
b = sqrt(324)
b = 18
This is the missing vertical leg of the triangle. And this is also the side opposite angle C.
We have enough information to compute the sine of the angle.
sin(angle) = opposite/hypotenuse
sin(C) = AB/AC
sin(C) = 18/82
sin(C) = (9*2)/(41*2)
sin(C) = 9/41
First we need to find the radius of the cylindrical tree trunk if the circumference C=4 feet: C=2rπ, r=4/(2π)=2/π. Now we find the volume V: V=r^2π*h, where h=20 feet is the height. So we input the numbers: V=(2/π)^2*π*20=(4/π²)*π*20. π in the nominator and the denominator cancel out: V=(4/π)*40=80/π. The volume of the cylindrical tree trunk is V=80/π feet^3